THE MASTER PROFESSIONAL AND ITS RELATION TO FIELD SCHOOL. (Fiep Bulletin - online, 2016)
This study aims to analyze the scientific production for the Field School in the Professional Master's programs. This type of master seeks to fill the gap left by the Academic Master, as regards the demand for educators that exists in the country. Thus, it consists of vocational training in which teachers can develop in your school environment a scientific research geared to producing materials that will allow an increase in the basic education of the schools in which they work, providing the dissemination of scientific knowledge generated at the gym. According to this scenario new programs within universities sit are created or existing programs are watching the landscape that grows around the discussion in the Field of Education theme developing in its thematic research lines in this area. These programs necessarily requires the effective presence of public universities. As a result of the involvement of universities in training activities, demanded by the Rural Education Movement, were constituting and consolidating several research groups, including the creation of master's research lines that only address the specifics of Rural Education, However, few in the educational context graduate. This paper analyzes, from the objectives of the professional master, end products for the Field Schools developed from dissertations of professional Masters Courses area of ??teaching and education. The purpose is to highlight the gap that exists within the Professional Master's programs in relation to scientific production aimed at the students of the field. The search for the adequacy of teaching practices that has as its foundation the context and the belonging of this subject before scientific knowledge requires the teacher the cultural domain historically situated to effectively overcome in building the relevant knowledge to these students.
Keywords: Masters Professionals; Rural Education and Scientific Production.